Interpretação e argumentação: uma aproximação à leitura de Paul Ricoeur - Tiellet, Claudia Aita (2014)
Paul Ricoeur identifies a position of antagonism between the theories of interpretation and argumentation within the contemporary legal thought. On one hand, the position of Ronald Dworkin and his proposed legal hermeneutics. Otherwise, the chain of legal arguments with Robert Alexy and Manuel Atienza. The examination of Ricoeur about this supposed antagonism seeks to show that the internal weaknesses of these two theoretical perspectives underpinning the proposal or the dialectical intersection of interpretation / argument in the judicial debate, as the author had done in other of his works with the couple to understand / explain the theories of text, action and history. The dialectic between argumentation and interpretation in the courts and the dialectic between explanation and understanding in terms of the theory of the text, the action and the story would be similar and not only restores the complex unity of the epistemology of legal debate, as ends the uncertainty introduced with the process which is crucial for legal certainty and the protection of our rights; which brings us to the seriousness of the act of judging. We can express these intersections wondering how the interpretive construction of a judicial decision is possible only insofar as it is also possible to argue for or against this or that interpretation and that requires not only a better understanding of the facts and the standard as the best (and formal) explanation, however, given the rules of any normative practical discourse, permeated by the ideals of correctness and universality, also implicit in the specific rules of legal discourse. Conclude, like Ricoeur, that the philosophical hermeneutic tradition that interprets texts to find the author's intent, would not be very different legal hermeneutics that seeks in the law the legislature's intention. The text, being autonomous, can be treated in two different ways: explained by its internal relations, by its structure or can afford to be completed by anyone who reads it, that is interpreted. However, these two methodologies imply one another and the purpose of the text (literary or legal) is to find the world that opens before the work. Thus, a proper dialectical understanding requires an explanation and the reverse path is equally necessary, because it aims at is the best interpretation - and the best court decision.